2020
DOI: 10.1093/femsec/fiaa061
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of stump removal and tree species composition on the diversity and structure of soil fungal communities

Abstract: Stump removal is a common forest management practice used to reduce the mortality of trees affected by the fungal pathogen-mediated root disease, Armillaria root rot, but the impact of stumping on soil fungal community structure is not well understood. This study analyzed the long-term impact of stumping and tree species composition on the abundance, diversity and taxonomic composition of soil fungal communities using internal transcribed spacer (ITS) marker-based DNA metabarcoding in a 48-year-old trial at Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Since root exclusion limits additional carbon into the soil, both communities may have to compete for the same limited resources, such as nutrients and space (Rousk et al 2008, Wang et al 2017). However, the low carbon requirements of fungi and their ability to breakdown complex recalcitrant molecules (Treseder and Lennon 2015, Poirier et al 2018), which are inaccessible to bacteria, makes fungi more resistant, and possibly leads to the stimulation of opportunist fungi (Lindahl et al 2010, Modi et al 2020). Similarly in a recent study by Merino‐Martín et al (2020), the influence of root traits on bacterial diversity was higher than for fungal communities, also Modi et al (2020) found that fungal alpha diversity in the topsoil increased significantly when roots were removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since root exclusion limits additional carbon into the soil, both communities may have to compete for the same limited resources, such as nutrients and space (Rousk et al 2008, Wang et al 2017). However, the low carbon requirements of fungi and their ability to breakdown complex recalcitrant molecules (Treseder and Lennon 2015, Poirier et al 2018), which are inaccessible to bacteria, makes fungi more resistant, and possibly leads to the stimulation of opportunist fungi (Lindahl et al 2010, Modi et al 2020). Similarly in a recent study by Merino‐Martín et al (2020), the influence of root traits on bacterial diversity was higher than for fungal communities, also Modi et al (2020) found that fungal alpha diversity in the topsoil increased significantly when roots were removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low carbon requirements of fungi and their ability to breakdown complex recalcitrant molecules (Treseder and Lennon 2015, Poirier et al 2018), which are inaccessible to bacteria, makes fungi more resistant, and possibly leads to the stimulation of opportunist fungi (Lindahl et al 2010, Modi et al 2020). Similarly in a recent study by Merino‐Martín et al (2020), the influence of root traits on bacterial diversity was higher than for fungal communities, also Modi et al (2020) found that fungal alpha diversity in the topsoil increased significantly when roots were removed. Our results support H1 that microbial diversity and composition will differ in root‐included and root‐excluded plots, for bacteria but not fungal diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Following harvest of diseased sites, the amount of fungal inoculum can be reduced, but not entirely eliminated, by removing infected stumps (Cleary et al, 2013; Morrison et al, 1988, 2014). That will increase survival of trees and improve their growth (Cleary et al, 2013; Morrison et al, 2014) because trees do not need to shift resource allocation from stem growth to active defence which they do when infected (Cruickshank et al, 2011) and because increases in ectomycorrhizal fungal associations following stump removal has been shown to be positively associated with tree productivity (Modi et al, 2020). It is notable that in the extra stump removal treatment at the Lussier site, no mortality occurred during 19 years following stump removal, compared with 12% and 14.3% losses in the thinned and control plots, respectively, where the stumps remained in place.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of intercropping are not limited to agricultural systems. Forest ecosystems, for example, develop disease-suppressive soils when trees are planted in multiple species as compared to monoculture [ 81 , 82 ].…”
Section: Agronomic Practices Phytomicrobiomes and Plant Diseasesmentioning
confidence: 99%